Effect of fibrous materials inclusion on the solid-state fermentation of post harvested wastes of Solanum tuberosum, - Borrás, L. M.; Valiño, Elaine; Elías, A.; Martínez, J. J.; Sanabria, A. M.; Becerra, Mónica (Cuban Journal of Agricultural Science, 2021)
In order to evaluate the solid-state fermentation of post-harvested wastes of S. tuberosum (potato), inoculated with a microbial preparation, analysis of variance was carried out according to a completely randomized design with factorial arrangement (3 x 3) for the fermentative indicators crude protein, true protein, dry matter, neutral detergent fiber, acid detergent fiber, pH, organic acids, lactic acid, NH3 and microbiological analysis. The factors were 15 and 25 % of inclusion of three fibrous plant material (wheat bran, alfalfa meal and rice meal) and three times of fermentation (0, 24 and 48 h) with three repetitions. The inclusion of 15 and 25 % of the different fibrous materials in the fermentations was performed under the same conditions, and showed interaction between the evaluated indicators and the fermentation time (P < 0.0001).The pH, dry matter, neutral detergent fiber and acid detergent fiber notably decreased in the three fibrous materials. There were lower values of lactic acid and ammonia (P < 0.0001) with dilution effect by the fiber. There were not pathogenic microorganisms, but there were significant values of acid lactic bacteria, at 48 h, in the mixture of alfalfa meal of 3.03 x 107 and 7.67 x 107 UFC/mL for 15 and 25 % of inclusion, respectively. The crude protein and true protein increased in 25 % with alfalfa and the dry matter reached at the end of the process 75.80 % for this treatment. It is concluded that the inclusion of fibrous materials in the solid-state fermentation of post harvested wastes of S. tuberosum, inoculated with a microbial preparation with acid lactic activity, have positive effect on their chemical and microbiological composition. It is recommended by the quality indicators of the final product, the use of 25 % of alfalfa meal, fermented at 20 °C during 48 h. Key words: potato, wheat bran, rice meal, alfalfa, lactic bacteria.